2020
DOI: 10.3389/fvets.2020.584436
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Lactobacillus-Based Teat Spray on Udder Health in Lactating Dairy Cows

Abstract: Teat disinfection is a common pre-and post-milking mastitis prevention practice that is part of a mastitis control program in dairy herds. Commercially available teat disinfectants are generally chemical-based products. The use of these products has occasionally raised concerns about the risk of chemical residues in milk. An alternative treatment or prevention strategy based on probiotics has the potential to circumvent this risk. Two treatments were compared in a cross-over clinical trial in a single herd: a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…Pesquisas recentes com "produtos naturais" desenvolvidos para higienização de tetos apresentaram resultados compatíveis com os aqui obtidos ao se comparar o uso de bacteriocinas (Klostermann, et al, 2010), probióticos (Yu, et al, 2017;Alawneh, et al, 2020), do extrato hidroalcoólico de T. minuta (Schiavon, et al, 2011), e de água ozonizada (Cavalcante, et al, 2013), quando comparado com uso de água, produto contendo iodo e produto contendo clorexidine, respectivamente.…”
Section: Resultsunclassified
“…Pesquisas recentes com "produtos naturais" desenvolvidos para higienização de tetos apresentaram resultados compatíveis com os aqui obtidos ao se comparar o uso de bacteriocinas (Klostermann, et al, 2010), probióticos (Yu, et al, 2017;Alawneh, et al, 2020), do extrato hidroalcoólico de T. minuta (Schiavon, et al, 2011), e de água ozonizada (Cavalcante, et al, 2013), quando comparado com uso de água, produto contendo iodo e produto contendo clorexidine, respectivamente.…”
Section: Resultsunclassified
“…Teat spray containing Lactobacillus spp. has a positive effect on mammary gland condition and improves the functions of the teat sphincter 47 . Adding probiotics to young stressed calves' diet can improve immunity response and alleviate acidosis in cows with rumen acidosis 48 .…”
Section: Probiotics In Ruminantmentioning
confidence: 99%
“…Studies also showed that by stimulating GH/IGF-1 hormone, both Bacillus subtilis and Bacillus amyloliquefaciens can upgrade intestinal maturation and growth competency [39]. Improved mammary gland condition along with the improved functions of the teat sphincter were observed by the effect of Lactobacillus base teat spray [40]. Chen et al [41,42] showed improved microbial fermentation and high rumen microbial growth performance by the addition of Rhodopseudomonas palustris.…”
Section: Probiotics In Ruminant Nutrition and Healthmentioning
confidence: 99%